Neuroimaging Assessment of Cerebrovascular Reactivity in Concussion: Current Concepts, Methodological Considerations, and Review of the Literature - Ellis, Michael J.; Ryner, Lawrence N.; Sobczyk, Olivia; Fierstra, Jorn; Mikulis, David J.; Fisher, Joseph A.; Duffin, James; Mutch, W. Alan C. (Frontiers in Neurology, 2016)
Concussion is a form of traumatic brain injury (TBI) that presents with a wide spectrum of subjective symptoms and few objective clinical findings. Emerging research suggests that one of the processes that may contribute to concussion pathophysiology is dysregulation of cerebral blood flow (CBF) leading to a mismatch between CBF delivery and the metabolic needs of the injured brain. Cerebrovascular reactivity (CVR) is defined as the change in CBF in response to a measured vasoactive stimulus. Several magnetic resonance imaging (MRI) techniques can be used as a surrogate measure of CBF in clinical and laboratory studies. In order to provide an accurate assessment of CVR, these sequences must be combined with a reliable, reproducible vasoactive stimulus that can manipulate CBF. Although CVR imaging currently plays a crucial role in the diagnosis and management of many cerebrovascular diseases, only recently have studies begun to apply this assessment tool in patients with concussion. In order to evaluate the quality, reliability and relevance of CVR studies in concussion, it is important that clinicians and researchers have a strong foundational understanding of the role of cerebral blood flow regulation in health, concussion and more severe forms of TBI, and an awareness of the advantages and limitations of currently available CVR measurement techniques. Accordingly, in this review we 1) discuss the role of CVR in TBI and concussion; 2) examine methodological considerations for MRI-based measurement of CVR; and 3) provide an overview of published CVR studies in concussion patients.